2021
DOI: 10.1029/2020jd033746
|View full text |Cite
|
Sign up to set email alerts
|

Constraining and Characterizing the Size of Atmospheric Rivers: A Perspective Independent From the Detection Algorithm

Abstract: ARs are associated with up to half of the extreme events in the top 2% of the precipitation and wind distribution across most midlatitude regions (Waliser & Guan, 2017). Moreover, landfalling ARs are associated with about 40%-75% of extreme wind and precipitation events over 40% of the world's coastlines (Waliser & Guan, 2017). ARs can have both positive and negative effects in continental regions. Their absence can lead to droughts (Dettinger, 2013), whereas numerous ARs can

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…The uncertainty in AR detection is key to answering this question. It has been discussed the possibility that there is more than one type of dynamical phenomenon that produces AR-like objects and that different definitions for these processes could help in future studies (Inda- Díaz et al, 2021;. This gains particular relevance for the study of future ARs in CWM, because, in general, different "types" of AR-like phenomena (including CWM landfalling tropical ARs) could have different responses to climate change.…”
Section: Discussionmentioning
confidence: 99%
“…The uncertainty in AR detection is key to answering this question. It has been discussed the possibility that there is more than one type of dynamical phenomenon that produces AR-like objects and that different definitions for these processes could help in future studies (Inda- Díaz et al, 2021;. This gains particular relevance for the study of future ARs in CWM, because, in general, different "types" of AR-like phenomena (including CWM landfalling tropical ARs) could have different responses to climate change.…”
Section: Discussionmentioning
confidence: 99%
“…The wide variety of accepted detection algorithms in the AR research community creates a dilemma in determining the truth to compare this algorithm to for verification. Due to the lack of agreement between ARTMIP algorithms and the types of algorithms used to calculate ARs (Inda‐Díaz et al., 2021; Zhang et al., 2021), it is necessary to compare CG‐Climate to additional common tracking methods to best understand its reliability. We compare the output of CG‐Climate to eight different ARTMIP algorithms (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…This is a common theme given that all AR detection algorithms have their own unique spatial biases. The training set used in this study used AR masks that were particularly larger than ARs detected from other studies (Inda‐Díaz et al., 2021). An extreme example of this happened on 3 January 2006 at 18Z (Figure 4) and serves as a useful case study to demonstrate this phenomenon.…”
Section: Methodsmentioning
confidence: 99%
“…How the relative dominance of wind and moisture will change through the lifecycle of ARs remains unanswered. Previous studies showed that landfalling ARs in different regions have various impact levels and distinct characteristics including genesis locations and AR sizes, and are connected to different large‐scale patterns (Inda‐Díaz et al., 2021; Prince et al., 2021; Zhou & Kim, 2019). Therefore, it is important to extend the discussion of AR flavors to the perspective of AR lifecycles and investigate whether the dominance of wind or moisture is constant throughout the lifecycle.…”
Section: Introductionmentioning
confidence: 99%